2012
DOI: 10.5399/osu/jtrf.47.3.2146
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic Value of Transit Accessibility: An Empirical Analysis in a Small Urban Area

Abstract: Many programs of the SAFETEA-LU have pointed to improving transit services and individuals' accessibility in small urban areas. Urban economic theory suggests that improving accessibility by investing in transportation has the potential to drive up bids for land. However, will the improved transit accessibility in small urban areas increase property values? A number of studies have investigated the impact of rail transit on home sales but produced mixed results. Further, few studies have explored how transit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Ignoring the presence of spatial autocorrelation would lead to biased and inconsistent parameter estimates. The traditional, plain linear regression that cannot tackle spatial effects (e.g., spatial autocorrelation and spatial heterogeneity) is not as acceptable as it used to be in spatial data modeling [49][50][51][52][53].…”
Section: Methodsmentioning
confidence: 99%
“…Ignoring the presence of spatial autocorrelation would lead to biased and inconsistent parameter estimates. The traditional, plain linear regression that cannot tackle spatial effects (e.g., spatial autocorrelation and spatial heterogeneity) is not as acceptable as it used to be in spatial data modeling [49][50][51][52][53].…”
Section: Methodsmentioning
confidence: 99%
“…Compared to non-residential properties, it is relatively easier to obtain the rental and sales data on residential properties. Specifically, researchers often use assessor's data, parcel data, or multiple listing service (MLS) data for residential properties (Iacono and Levinson 2011;Hess and Almeida 2007), and rental rates can be obtained from self-administered surveys or rental offices of apartment complex (Bina, Warburg, and Kockelman 2006;Cao and Hough 2008).…”
Section: Limited Efforts On Non-residential Propertiesmentioning
confidence: 99%
“…Cao and Hough (2012) found that in North Dakota, buses had no significant impact on land value. The impact was even negative within 200 m of a bus stop.…”
Section: Literature Reviewmentioning
confidence: 95%